Amperometric Glucose Sensor Based on The Entrapment of Glucose Oxidase in Electrochemically Synthesized Pyrrole/ N,N-Dimethylaminopyrrole (Py/DMAPy) Copolymer Film - SEN, S. (Asian Journal of Chemistry, 2010)
Glucose oxidase (GOx) was entrapped on the films obtained by electrochemical copolymerization of pyrrole (Py) and N,N-dimethylaminopyrrole (DMAPy), to fabricate GOx-immobilized electrodes for amperometric sensing of glucose. Polymeric film was characterized with cyclic voltammetry (CV) and Fourier transform infrared (FTIR) spectroscopy. The amperometric response of the enzyme electrode was measured at +0.70V vs. Ag/AgCl, which was due to the electrooxidation of enzymatically, produced H2O2. The effects of the composition of copolymer, pH, temperature and substrate concentration on the response of the enzyme electrode were investigated. The optimum pH was found to be 7.4 at 25 ºC and response time of enzyme electrode was determined as 45 s. The upper limit of the linear working portion was obtained as 10 mM glucose concentration with a detection limit of (5.0 × 10-6 M) with the calculated value of apparent Michaelis-Menten constant (KMapp) was 3.70 mM. The activation energy of this immobilized enzyme system were found to be 30.25 kJ mol-1.